The Causes of Insulting Religious Sanctities Among People and Its Consequences - Saem, Sebghatallah (Integrated Journal for Research in Arts and Humanities, 2024)
This research paper has been prepared analytically with the aim of identifying the causes of insulting religious sanctities among humanitarian societies throughout the history and the factors that go beyond the great historical events among them, which led to great upheaval. The paper starts with definition of insulting religious sanctities. Then presents a historical overview of insulting the sanctities of religion and its consequences. Next, it analyzes the causes of insulting religions and social values. Also, it presents the position of Islam against insulting and offensive reactions to social values and religious sanctities. Finally, it argues that the concept of freedom of expression has been abused by some people in most religious societies as well as in some nonreligious societies, while this freedom is subject to certain restrictions for the purpose of maintaining public order.